2022
DOI: 10.1177/13607804221117835
|View full text |Cite
|
Sign up to set email alerts
|

Swiping as a Single Mom: A First Look at the Experiences of Single Mothers Who Use Tinder

Abstract: Single mothers who wish to find new dating partners must contend with a lack of free time and the demands of parenting. As online dating has become a more socially acceptable way to access social, romantic, and sexual opportunities, many single mothers are now considering the use of dating apps to pursue their goals. In this article, we explored the vocabularies of motive of single mothers who used the dating app Tinder. For this purpose, we applied the foundational theory of situated action and vocabularies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Most of the prior literature on dating applications has exclusively focused on Tinder. Given its huge popularity across the globe [ 39 , 55 , 56 ], it is not surprising that most of the prior researchers have specifically focused on Tinder [ 14 , 18 , 51 , [57] , [58] , [59] , [60] , [61] ]. A recent meta-analysis of 70 studies on dating applications has revealed that 35 % of the studies were Tinder-specific [ 2 ].…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%
“…Most of the prior literature on dating applications has exclusively focused on Tinder. Given its huge popularity across the globe [ 39 , 55 , 56 ], it is not surprising that most of the prior researchers have specifically focused on Tinder [ 14 , 18 , 51 , [57] , [58] , [59] , [60] , [61] ]. A recent meta-analysis of 70 studies on dating applications has revealed that 35 % of the studies were Tinder-specific [ 2 ].…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%